2012
DOI: 10.1155/2012/694629
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Translocation in Chronic Liver Diseases

Abstract: The intestinal microflora is not only involved in the digestion of nutrients, but also in local immunity, forming a barrier against pathogenic microorganisms. The derangement of the gut microflora may lead to microbial translocation, defined as the passage of viable microorganisms or bacterial products (i.e., LPS, lipopeptides) from the intestinal lumen to the mesenteric lymph nodes and other extraintestinal sites. The most recent evidence suggests that microbial translocation (MT) may occur not only i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 160 publications
1
59
1
7
Order By: Relevance
“…This is in contrast to an early cross sectional study that showed that elevated LPS was independently associated with cirrhosis 10 as well as several studies examining sCD14 levels (including our own) which reported that elevated levels of sCD14 were associated with a increased risk of liver disease progression in patients with and without HIV 9,10,44,45 . The difference in outcomes is perhaps due to difference in study design, population, or the endpoints defining liver disease progression, or related to the low proportion of patients in the current study that reported hazardous alcohol consumption.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast to an early cross sectional study that showed that elevated LPS was independently associated with cirrhosis 10 as well as several studies examining sCD14 levels (including our own) which reported that elevated levels of sCD14 were associated with a increased risk of liver disease progression in patients with and without HIV 9,10,44,45 . The difference in outcomes is perhaps due to difference in study design, population, or the endpoints defining liver disease progression, or related to the low proportion of patients in the current study that reported hazardous alcohol consumption.…”
Section: Discussioncontrasting
confidence: 99%
“…Such results are consistent with previous studies [1,21,22]. Second, from the perspective of the intestinal bacterial flora, overgrowth has been shown to frequently occur during severe trauma or large operation [4,23] or liver diseases [24]. And apical exposure to LPS could increase epithelial permeability in the intestine [25], involving disruption of tight junction [26,27].…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with our results, the UDCA + NAC combination had the least lowering potential regarding TNF-a level and was not as effective as UDCA alone (Belonovskaia et al, 2013). It should be mentioned that cultures of samples from portal blood, peripheral blood, and perihepatic lymph nodes in our model were negative in all groups, proving that expression of hepatic TNF-a was not due to bacterial translocation but due to MCDD (Pinzone et al, 2012).…”
Section: Discussionmentioning
confidence: 71%